An Analysis Upon Awareness, Knowledge and Attitude Among High School Students: a Case Study of Environmental Education: Evaluating Awareness, Knowledge, and Attitudes of High School Students towards Environmental Education (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The importance of environmental education (EE) is well known globallyamong societies. Environmental education is gradually promoted as a sustainabletool in protection of the environment Environmental education is found acrossschool curriculums in India. The objectives of the curriculum are environmentalattitude, knowledge and awareness (AKA) where has been investigated in thecurrent study. Throughout the final 30 years, environmental training has been part ofthe curriculum in Southwest Florida open schools. Curriculum goals, forexample, environmental mentality, information, and cognizance (AKA), have beenexamined in the literary works as courses to enhance the on the whole conductof destiny residents in the direction of the environment. The motivation behindthis study was to assess the previously stated goals right around the emulatingassemblies: environmental experts, secondary school teachers, High Schoollearners, and the guardians of the comparing understudies in three SouthwestFlorida regions throughout the 2003-2004 school year. An instrument wasadvanced to measure the gatherings' levels of mindfulness, information, andmentality and their levels of self-viability. The turned around studies actedfor reactions from: 27 earthy experts, 15 High Schoolteachers, 224 High Schoolunderstudies, and 222 guardians. This study recognized statistically noteworthydistinctions around the gatherings observing the levels of cognizance,learning, and demeanor as identified with ecological issues. The naturalmasters scored most noteworthy for all AKA segments as contrasted with theleast levels displayed by guardian mindfulness, guardian disposition, and HighSchool person learning. What's more, elements for example socioeconomic status,ethnicity, and inclination of recreation actions brought about contrasts rightaround the aggregations noticing their levels of environmental AKA. This studybackings the assessment of AKA levels right around members as a proper approachto the assessment of environmental curriculum targets. What's more, the studyinfers a re-ordered estimation of AKA as an endeavor to unify the parametersmeasured by various instruments discovered all through environmental trainingwriting. The outcomes of this study may help environmental authorities,teachers, and school regions in the assessment of environmental instructioncurricula. The study concluded that a high level of awareness and knowledge pluspositive attitude of students may come have been achieved from the families ofrespondents, teachers, media, private reading and school curriculums regardingthe environment that increases the environmental view among students as well asoverall in the society.